Survival time and prognostic factors of AIDS patients in Kelantan : 2010-2014 - Ngah, Hamiza (2018)
Background: The AIDS death is still a worldwide concern as well as in Kelantan. However, the median survival time and predictor factors that contributing to risk of death among AIDS patients in Kelantan were unknown. Objectives: To determine the overall median survival time and survival rate of AIDS patients and predictors factors of death in Kelantan population from 2010 to 2014. Methodology: A retrospective cohort study was conducted in January 2018 using secondary data obtained from National AIDS Registry for the period of 1st January 2010 to 31st December 2014 and followed-up until 31st Mac 2015. A complete 1073 data was selected for descriptive analysis and survival analysis. Kaplan- Meier survival analysis and Cox’s proportional hazard regression model with estimates of hazard ratio and 95% confidence interval were used. Result: The mean (SD) age was 37.08 (7.37). The patients were predominantly males (87.0%), Malays (87.5%), single (62.3%), unemployed (38.0%), with background of secondary education (78.1%) and cases without HIV-TB co-infection (62.8%). Approximately 53% of the patients death during follow-up. The overall median survival time was 11 months. The probability of survival in 1-year, 2-year and 5-year were 49.1%, 47.8%, and 46.7% respectively. Multivariate Cox regression showed that significant prognostic factors were age 30-49 years (Adj. HR 1.57; 95% CI: 1.14, 2.16; p=0.006), male (Adj. HR 1.39; 95% CI: 1.07, 1.79; p=0.012), unemployed (Adj. HR1.40; 95% CI: 1.12, 1.75; p=0.003) and HIV-TB co-infection (Adj. HR 1.78; 95% CI: 1.37, 2.31; p<0.001). Conclusion: The overall median survival time among AIDS patients in Kelantan was still low. To increase the survival among AIDS patients, every effort need to be made to ensure early screening, early diagnosis, early intervention and comprehensive management involving initiating HAART treatment as soon as possible in treating HIV/AIDS patients before they progress to AIDS-related death.